Socioeconomic status and dialysis quality of care. Issue 5 (21st July 2019) - Krishnasamy, Rathika; Jegatheesan, Dev; Lawton, Paul; Gray, Nicholas A
ABSTRACT: Aim: Lower socioeconomic status (SES) has been associated with increased dialysis mortality. This study aimed to determine if the quality of care (QOC) delivered to dialysis patients varied by SES. Methods: All non‐Indigenous adults commencing haemodialysis (HD) or peritoneal dialysis (PD) registered with the Australia and New Zealand Dialysis and Transplant Registry between 2002 and 2012 were included. Each patient's location at dialysis start was classified into SES quartiles of advantaged to disadvantaged. Guidelines were used to determine attainment of adequate QOC at 6–<18 months and 18–<30 months after dialysis start, using logistic regression models. QOC measures included pre‐dialysis phosphate, calcium, haemoglobin, transferrin saturation and ferritin. HD‐related parameters included single pool Kt/V and percentage with functioning arteriovenous fistula/graft. PD‐related parameters included weekly Kt/V and percentage transferring to HD. Results: Of 19 486 commencing dialysis, the median age was 65 years (interquartile range 53–74), 62.2% were male and 85.1% were Caucasian. At 6–<18 months after dialysis start, there were no significant differences by SES in attainment of biochemical targets, PD or HD adequacy. The disadvantaged quartile was less likely to achieve haemoglobin targets (odds ratio 0.88, 0.80–0.96, P = 0.01) or have a functioning arteriovenous fistula or graft (odds ratio 0.79, 0.68–0.92, P = 0.003) compared with the most advantaged group. Vascular access differences persisted at 18–<30 months. Conclusion: Other than vascular access, area‐level SES has minimal impact on QOC attainment among non‐Indigenous dialysis patients in Australia. Increased mortality in lower SES groups may be due to pre‐dialysis factors and other variables such as health‐related behaviours, lifestyle and literacy. SUMMARY AT A GLANCE: This study was designed to test whether the quality of care delivered to dialysis patients varied by socioeconomic status among 19 486 patients commencing haemodialysis or peritoneal dialysis between 2002 and 2012, as recorded in Australia and New Zealand Dialysis and Transplant Registry (ANZDATA). The conclusion showed socioeconomic status has minimal impact on quality of care. Increased mortality in lower SES groups may be due to pre‐dialysis factors and other variables such as health‐related behavior, lifestyle and literacy.